(untitled) (Development Service Industry Management, 2024)
The article is devoted to the generalization and further development of the theoretical and methodological foundations of the study of the essential characteristics of the economic security of the enterprise. The purpose of the research is the structuring of scientific views and the further development of the theoretical and methodological foundations of the study of economic security of the enterprise. A critical review of the approaches of various authors to the interpretation of the concept of "economic security of the enterprise" was carried out. An approach to the grouping of scientific views on the interpretation of the concept of economic security of the enterprise is proposed. The author’s vision of the concept and structural and content characteristics of the economic security of a business entity is substantiated. A new vision of the basic provisions in the field of economic security management of enterprises and organizations has been developed. It was established that the economic security of the enterprise is a unique systemic characteristic of its ability to survive in difficult economic conditions. It is shown that many approaches have been developed to date, both to essential interpretation and to structural decomposition, research and analysis methods, determination of mechanisms, tools and means of strengthening. At the same time, it was stated that the improvement of the acquired knowledge continues to this day and this means that unified approaches and practices have not yet been developed. According to the author’s position, it is proposed to interpret the economic security of the enterprise as a state in which the enterprise functions stably and develops in accordance with operational and strategic development plans, its activities are adequately protected from external and internal challenges, risks and threats, the economic interests of the enterprise’s stakeholders (its owners) are realized and founders, top management and staff, strategic investors and business partners). It was revealed that the substantive characteristics of the so-called second level of economic security of the enterprise should be considered to be the provision of all functional and resource components of security, financial and economic stability, profitability and capitalization, quality of financial and economic intelligence, protection of commercial secrets and countering economic espionage, building up and effective use of intellectual - personnel potential, a high level of innovative activity and investment in progressive technological innovations.